The expected labor progression after labor augmentation with oxytocin: A retrospective cohort study. - Lin Zhang; James Troendle; D Ware Branch; Matthew Hoffman; Jun Yu; Lixia Zhou; Tao Duan; Jun Zhang (PLoS ONE, 2018)
OBJECTIVE:To describe labor progression patterns with oxytocin for augmentation in women who achieve vaginal delivery; and to determine how long one should wait with effective uterine contraction before labor arrest can be diagnosed. DESIGN:Population-based retrospective cohort study. POPULATION:The final sample involved 8,988 women with singleton gestation, term live birth, vertex presentation, no previous cesarean section, vaginal delivery, and neonatal Apgar score at 5 minutes at 7 or higher, and complete information on oxytocin augmentation in 2005-2007. METHODS:Linear interpolation was used from the vaginal exam records for each woman to estimate the cervical dilation when oxytocin was started and the highest dose was first reached by parity. We used survival methods to estimate quartiles of the traverse time distributions of cervical dilation. MAIN OUTCOME MEASURES:Duration of labor under oxytocin augmentation. RESULTS:When oxytocin was just started, it took a long time to observe cervical dilation. The 50th(95th) centiles of the time interval from 4 to 5 cm, 5 to 6 cm, and 6 to 10 cm dilation were 2.9(8.8) hr, 1.7(5.8) hr, and 2.1(6.0) hr in nulliparas; and 3.1(10.1) hr, 1.9(8.0) hr, and 1.7(6.2) hr in multiparas. After effective uterine contractions were achieved under oxytocin, labor progressed much faster. The corresponding values were 0.7(2.4)hr, 0.5(1.5)hr, and 0.5(1.5)hr in nulliparas; and 0.6(1.9)hr, 0.4(1.1)hr, and 0.4(0.9)hr in multiparas. Low- and high-dose oxytocin regimens had similar effects on labor. CONCLUSION:When oxytocin is just started for labor augmentation in early first stage, it may take up to 10 hours for the cervix to dilate by 1 cm. Once effective uterine contractions are achieved and the cervix is dilated more than 5 cm, cervical dilation to the next centimeter occurs within 2 hrs in both nulliparas and multiparas in 95% of the cases. High- and low-dose oxytocin had a similar impact on labor progression in augmented labor.